Cyclic GMP-AMP Synthase Is Required for Cell Proliferation and Inflammatory Responses in Rheumatoid Arthritis Synoviocytes - Yan Wang; Guo-Hua Su; Fang Zhang; Jing-Xue Chu; Yun-Shan Wang (Mediators of Inflammation)
Rheumatoid arthritis (RA) is characterized by inflammatory cell infiltration, fibroblast-like synoviocytes (FLS) invasive proliferation, and joint destruction. Cyclic GMP-AMP synthase (cGAS) is a cytosolic DNA sensor that induces immune activation. In this study, we examined whether cGAS plays a role in RA FLS. In this study, cGAS was overexpressed in RA-FLS compared with OA FLS. TNFα stimulation induced cGAS expression in RA FLS. Overexpression of cGAS promoted the proliferation and knockdown of cGAS inhibited the proliferation of RA FLS. cGAS overexpression enhanced the production of proinflammatory cytokines and matrix metalloproteinases (MMPs) as well as AKT and ERK phosphorylation in TNFα-stimulated FLS. In contrast, cGAS silencing inhibited production of proinflammatory cytokines and matrix metalloproteinases (MMPs) as well as AKT and ERK phosphorylation in TNFα-stimulated FLS. These results suggest that cGAS activates the AKT and ERK pathways to promote the inflammatory response of RA FLS, and the development of strategies targeting cGAS may have therapeutic potential for human RA.